Cybersecurity and Cyber Defence: Nationwide Level Strategic Method (Global Journal of Computer Science and Technology, 2023)
Data working knowledge OT and an extensive range of other practices tools and concepts are all comprised under the canopy term of cybersecurity The aggressive use of info skill to bout opponents is a characteristic eye of cyberse-curity Clienteles and security doctors are misinformed and the significant changes between these sentences are hidden by the use of the term cybersecurity as a key challenge and a substitute for info security or IT security The period cybersecurity should only be used to mention to security practices related to self-justifying actions involving or relying on info skill and or working knowledge surroundings and schemes according to the orientation of security leaders In this paper we define cyberse-curity and thoughtful how info security
Keywords: Action plan; cyberattack; cybercrime; cyber defence; cyber operations; cybersecurity; national cybersecurity strategy; people-centric security